2021
DOI: 10.7150/thno.52848
|View full text |Cite
|
Sign up to set email alerts
|

PHB2 promotes tumorigenesis via RACK1 in non-small cell lung cancer

Abstract: Background: Lung cancer has the highest mortality rate among cancers worldwide, with non-small cell lung cancer (NSCLC) the most common type. Increasing evidence shows that PHB2 is highly expressed in other cancer types; however, the effects of PHB2 in NSCLC are currently poorly understood. Method: PHB2 expression and its clinical relevance in NSCLC tumor tissues were analyzed using a tissue microarray. The biological role of PHB2 in NSCLC was investigated in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…However, the context-dependent role of RACK1 in lung cancer remains controversial [ 16 , 35 ]. In the current study, we found that loss of RACK1 inhibits the proliferation, migration and invasion abilities of NSCLC cells, consistent with most currently published papers [ 36 ]. Our research further validated the oncogenic role of RACK1 in NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…However, the context-dependent role of RACK1 in lung cancer remains controversial [ 16 , 35 ]. In the current study, we found that loss of RACK1 inhibits the proliferation, migration and invasion abilities of NSCLC cells, consistent with most currently published papers [ 36 ]. Our research further validated the oncogenic role of RACK1 in NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, R software package was used to analyze the coexpression genes of NPM1 in LUAD, and it was found that the expressions of RACK1, BTF3, RPL26L1 and NHP2 in LUAD had the strongest correlation with NPM1. Wu et al (40) found that PHB2 promotes tumorigenesis via RACK1 in non-small cell lung cancer. Jeon et al (41) found that kahweol inhibited the proliferation of NSCLC cells through ERK-mediated signaling pathways and the downregulation of BTF3, while the role of RPL26L1 and NHP2 in LUAD has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid reduction of HDAC1 and RACK1 during FH induction was suggestive of ubiquitin-proteasome-dependent degradation. Recent studies suggested that RACK1 might also undergo ubiquitination under specific circumstances 48 - 50 . Our quantitative RT-PCR data also indicated that Hdac1 and Rack1 mRNA levels were unchanged under the same conditions (Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%